The importance of automation in the Onfarm Bioinputs multiplication process - Assis, Lucas Vinícius; Silva, Eric Valero Carvalho da (Research, Society and Development, 2023)
This article aims to analyze the importance of automation in the onfarm bioinputs multiplication process, highlighting its benefits for sustainable agriculture. The methodology used in the research was a narrative bibliographic review, aiming to understand how automation can optimize the production of bioinputs. The results demonstrate that automation increases efficiency, reduces production time, and improves the quality of biological inputs. Moreover, the use of automated systems contributes to cost reduction and more efficient use of agricultural resources. In conclusion, automation plays a fundamental role in enabling the multiplication of bioinputs, driving the adoption of sustainable onfarm agriculture. This approach has the potential to promote environmentally friendly agricultural practices and contribute to increased productivity and food security.